2020
DOI: 10.1055/s-0040-1708096
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis during the Pregnancy-Puerperal Cycle - Literature Review

Abstract: Objective To identify current strategies and recommendations for venous thromboembolism prophylaxis associated with the pregnancy-puerperal cycle, a condition of high morbidity and mortality among women. Methods The literature search was performed between May and October 2019, using the PubMed database, including papers published in Portuguese, English and Spanish. The terms thromboembolism (Mesh) AND pregnancy (Mesh) OR postpartum (Mesh) were used as descriptors, including randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 41 publications
(95 reference statements)
0
15
0
1
Order By: Relevance
“…Thus, there is a difference in the situation when the patient has a history of unprovoked VTE or an episode of VTE associated with transient risk factors ( Table 2 ) [ 70 ].…”
Section: When To Use Antithrombotic Prophylaxismentioning
confidence: 99%
“…Thus, there is a difference in the situation when the patient has a history of unprovoked VTE or an episode of VTE associated with transient risk factors ( Table 2 ) [ 70 ].…”
Section: When To Use Antithrombotic Prophylaxismentioning
confidence: 99%
“…The protocol below describes the specific steps for isolating and freezing PBMCs from pregnant patients. The challenge of the procoagulant state of pregnancy ( Sanches et al., 2020 ) (including an increase in clotting factors, reduced anticoagulant and fibrinolytic activity) made density centrifugation difficult, as the plasma layer was stained with blood. We found that use of EDTA in PBS to the blood before centrifugation improved separation and yield.…”
Section: Before You Beginmentioning
confidence: 99%
“…This can be seen in Figure 1 , which demonstrates a comparison of diluted blood samples with PBS without EDTA ( Figure 1 A) and the addition of 1 mM of EDTA ( Figure 1 B). We considered the differences in haemostatic profile in pregnant women vs healthy controls – during pregnancy, the significant increase in clotting factors, reduced quantity of anticoagulants and reduced fibrinolytic activity creates a state of hypercoagulability ( Sanches et al., 2020 ). This likely makes density centrifugation more complicated, and why the anticoagulant EDTA helped reduce blood contamination.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…É importante que as mulheres adotem um padrão alimentar, no período de amamentação, pois uma dieta mista, podem desacelerar o processo de perda de peso (Gomes et al, 2021;Souza, 2015;Sanches et al, 2020).…”
Section: Estratégia Nutricional Para Recuperação De Peso No Pós-partounclassified